Threefold manuscripts: the nine texts of the Florentine Codex. - Dufendach, Rebecca (Colonial Latin American Review, 2023)
To understand the manuscript creation process practiced by Indigenous intellectuals in the Americas this essay examines the work of the Nahua scholars who, along with Bernardino de Sahagún, created the Florentine Codex (1575–1577). Now fundamental to studies of the Codex is an evaluation of its three 'texts': the Nahuatl-language alphabetic text, the Spanish-language annotations including loose translations, and its bountiful images. Two sources served as iterative kinds of drafts for the Codex project: the Primeros memoriales (1558–1561) and the Manuscrito de Tlatelolco (1561–1566). Each of the manuscripts contains its own three texts, thus they are threefold, that enable an examination of nine separate but interrelated source texts. In considering the differences among the cumulative nine texts, this article uncovers new insights into an unstudied process of negotiation between the Nahua scholars, the elders whom they consulted, and their Spanish colleagues. As sites of mediation among colonial actors, the threefold manuscripts manifest on their folios the competing interests and agendas that shaped the production of knowledge in New Spain.